Company of images : modelling the imaginary world of Middle Kingdom Egypt (2000-1500 BC) - Miniaci, Gianluca; Betro, Maria C.; Quirke, Stephen. (Orientalia Lovaniensia analecta, 2017)
From prehistoric figurines and graffiti to modern digital photographs, human beings repeatedly produced images, transforming the world itself into a relentless fabric of images. This volume presents the proceedings of the international conference held at the Institute of Archaeology - UCL, London in 2014 inside the framework of the European project 'EPOCHs', with the aim to explore the fertile imaginary world of Middle Bronze Age Egypt (2000-1500 BC). The final goal is to highlight theoretical and methodological issues in order to explore connections between the images and their society, people who created images and who were recursively affected by the images they created.